(untitled) (Revista Paradigma, 2022)
The present study has its general objective to analyze if article 394-A of the CLT, questioned in ADI 5938, represents a deficient protection of the State, based on the duty of protection and the theories of restrictions on Fundamental Rights, in order to answer the following research problem: from the perspective of the theory of the duty of protection of fundamental rights, how can state interventions by Legislative Power (regarding article 394-A, CLT) and Judiciary (Supreme Court in ADI 5938) be assessed in reference to maternity and childhood protection? As a research hypothesis, it is understood that the Law n. 13.467/2017, by conditioning the removal of pregnant and lactating employee from unhealthy place to the presentation of medical certificate, ended up violating the right to protection of maternity provided in the Federal Constitution. In this sense, based on the duty of protection` theory of fundamental rights, the legislative intervention represents a insufficient state protection. Thus, the performance of the Federal Supreme Court, when the ADI 5938 was judged, by declaring the aforementioned article device unconstitutional, represented the positive performance of the State as a protector of fundamental rights. In the end, it was concluded that the research hypothesis was confirmed. The research was developed by the deductive approach method and by the indirect documentation research technique, through bibliographic research.